A Utilização de uma sequência didática sobre saneamento básico para o ensino de biologia - Spiandorin, Marcello (2019)
Basic Sanitation (BS) in recent years is one of the main issues when it comes to physical, mental and social well-being, and its deficiency can affect the personal, professional and social environment of the entire population. The school has a fundamental role in the formation of society and through education and knowledge sharing can form citizens more aware of their rights and duties. Due to the importance of the theme to society and the fact that it was cited in the main external evaluations, such as the Exame Nacional do Ensino Médio (ENEM) and the lack of material contextualizing the different areas of Biology, a Didactic Sequence (DS) was developed. Activities focusing on the theme BS and using different methodologies that highlighted its importance and consequences of its deficit for society and the environment verifying its contribution to the learning of this theme by students. DS was applied to a twelfth grade at a state regular school located in the Capuan district, Caucaia, Ceará. Before starting the DS, students answered a Pre-Test containing questions related to the BS theme taken from ENEM and the main entrance exams in Brazil. Eight classes of the proposed DS were applied and after the application, the students again performed a Post-Test on the subject where the improvement in the evaluation result was over 93% compared to the initial test. Through the application of this DS, it was possible to verify how this theme is present in the daily life of society in general and how it is little worked together and interdisciplinary in schools and that the applied DS had its validity and could serve as a basis for use by other teachers and school units.